2014
DOI: 10.1002/yea.3026
|View full text |Cite
|
Sign up to set email alerts
|

Variation inα-acetolactate production within the hybrid lager yeast groupSaccharomyces pastorianusand affirmation of the central role of theILV6gene

Abstract: A screen of 14 S. pastorianus lager-brewing strains showed as much as a nine-fold difference in wort total diacetyl concentration at equivalent stages of fermentation of 15°Plato brewer's wort. Two strains (A153 and W34), with relatively low and high diacetyl production, respectively, but which did not otherwise differ in fermentation performance, growth or flavour production, were selected for further investigation. Transcriptional analysis of key genes involved in valine biosynthesis showed differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…The catalytic subunit is encoded by ILV2 and the regulatory subunit encoded by ILV6 a gene located on CHRIII. Although the ILV6 copy number has been associated with variation in diacetyl production in S. pastorianus , a reduction in copy number was associated with lower diacetyl (Duong et al, 2011 ) while overexpression of either of the ILV6 alleles led to increased diacetyl formation (Gibson et al, 2015 ). These results would disagree with the results of this study which would associate a doubling of SeILV6 copy number with a reduction of diacetyl.…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic subunit is encoded by ILV2 and the regulatory subunit encoded by ILV6 a gene located on CHRIII. Although the ILV6 copy number has been associated with variation in diacetyl production in S. pastorianus , a reduction in copy number was associated with lower diacetyl (Duong et al, 2011 ) while overexpression of either of the ILV6 alleles led to increased diacetyl formation (Gibson et al, 2015 ). These results would disagree with the results of this study which would associate a doubling of SeILV6 copy number with a reduction of diacetyl.…”
Section: Discussionmentioning
confidence: 99%
“…Proteome and transcriptome studies have, however, shown that significant differences in subgenome activity can occur in lager yeast (Caesar et al 2007; Horinouchi et al 2010; Minato et al 2009; Yoshida et al 2007), suggesting that gene regulation in interspecies hybrids is not seamlessly integrated across subgenomes. Gibson et al (2015) showed that differences in expression of the two different alleles of the regulatory gene ILV6 in S. pastorianus could influence strain phenotypes (in this case, the production of α-acetolactate). Otherwise, there was no functional difference between the gene products as determined by their over-expression with the same promoter.…”
Section: Hybrid Genome Function and Stabilitymentioning
confidence: 99%
“…These acids are intermediates in the synthesis of valine and isoleucine, respectively. The amounts and profile of α ‐acetohydroxyacids produced during fermentation are influenced by yeast strain, medium composition, and fermentation conditions (Dufour et al, ; Brányik et al, ; Gibson et al, ). It is also suggested that VDK formation is linked to amino acid metabolism.…”
Section: Biochemistry Of Flavour Production In Yeastmentioning
confidence: 99%